Understanding the Influence of Teacher Beliefs in Shaping Filipino Professoriate’s Signature Pedagogy for Teacher Education - Fadera, Virgilio; De Guzman, Allan (Romblon State University Research Journal, 2014)
Using the phenomenological design of qualitative inquiry, this study sought to describe how teacher beliefs become instrumental in shaping a dsitinct pedagogy for teacher education. Interestingly, this investigation surfaced the trilogy of influence typologies that shape Filipino professoriate’s distinctive teaching apporaches for teacher education, namely: contextualizing, configuring and concretizing power. Findings concurred with literature which recognizes the strong impact of teacher beliefs on instructional practices, highlighting the influence of beliefs in shaping signature pedagogies. To deepen understanding of teacher education’s signature pedagigy and how it is shaped by teacher beliefs, further research along the line of inquiry is recommended, particularly in other educational and cultural communities.